The construction of the health professional in palliative care contexts: a scoping review on caring for the person at the end of life - Parola, Vitor (Porto Biomed J, 2018)
AIM: The aim of the study was to map of the literature on the elements contributing to the construction of the health care professional in the context of palliative care. METHODS: Scoping review based on Arksey and O’Malley framework. PubMed, Embase, CINAHL, Scopus databases, and gray literature were the sources searched (2005–2015), completed by reference searching, hand searching, and expert consultations. Primary studies focusing on different professionals working in palliative care units or hospice centers were eligible for inclusion. RESULTS: From a total of 3632 articles, 22 met the inclusion criteria. The content of the studies was described and classified in 5 elements: (i) construction and application of the concept of care; (ii) psychosocial effects that the daily care produces; (iii) working conditions that influence the caregiving provided; (iv) knowledge mobilized in the provision of care; and (v) strategies adopted by health care professionals to build relationships. Data about nurses, physicians, and psychologists were found, but no data were found about social workers. Gaps identified in the publications were as follows: relationship competencies and strategies adopted; the real needs from educational programs; and the view of other professionals. CONCLUSIONS: Key elements identified in the concept of the construction of the health care professional should be addressed in future interventions: prevention of emotional exhaustion, depersonalization, and achievement of a greater personal accomplishment. In addition, none of the articles retrieved offered the different perspectives of all the disciplines in a multidisciplinary team.